Effect of Salinity on Prosopis juliflora during Early Growth Phase - Somashekhar, R. (Indian Forester, 1998)
Prosopis juliflora, a popular firewood species was exposed to salinity artificially in the laboratory and field experiment. The mild dose (0.5 and 1.0%) has stimulated growth and biomass parameters. It was found that salinity effect was more in germination than later stage i.e. 6 month and 1 year.